Kyla Cherry - Bandler, John (Bandler Corporation, 2009)
A fan’s seemingly chance meeting with Kyla Cherry, cable news’s sexiest anchor, turns out to have been decreed, and is key to the inevitable Revolution against the Archive.
This short story, a fantasy, explores the tension between individual free will and desire, and totalitarian control.
Keywords: short story; fantasy; science fiction; totalitarianism; Wikipedia; the human condition; lust; obsession